2008
DOI: 10.1007/s12325-008-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GnRH agonists and antagonists in normoresponder IVF/ICSI in Turkish female patients

Abstract: GnRHant and GnRHa provide comparable results in normoresponder patients, while GnRHant allows a greater flexibility in their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Several authors [20,32,33] reported a significant decrease in pregnancy rate for the antagonist compared to the agonist, although many clinical studies [34,35] have reported no differences in pregnancy rates between the antagonist and agonist groups, In conclusion, because the numbers of collected oocytes and mature oocytes are good parameters qualifying follicular maturation, our overall data seem to reflect a better follicular growth and oocyte maturation after triptorelin treatment. However, both regimens seem to have similar efficacy in terms of implantation and pregnancy rates, as reported by other authors [10,36,37]. The role of GnRH antagonists in ovarian stimulation for IVF appears to be promising, although many questions regarding preferred dose regimens and effects on clinical outcomes remain.…”
Section: Discussionsupporting
confidence: 65%
“…Several authors [20,32,33] reported a significant decrease in pregnancy rate for the antagonist compared to the agonist, although many clinical studies [34,35] have reported no differences in pregnancy rates between the antagonist and agonist groups, In conclusion, because the numbers of collected oocytes and mature oocytes are good parameters qualifying follicular maturation, our overall data seem to reflect a better follicular growth and oocyte maturation after triptorelin treatment. However, both regimens seem to have similar efficacy in terms of implantation and pregnancy rates, as reported by other authors [10,36,37]. The role of GnRH antagonists in ovarian stimulation for IVF appears to be promising, although many questions regarding preferred dose regimens and effects on clinical outcomes remain.…”
Section: Discussionsupporting
confidence: 65%
“…Some methods have been suggested for AH such as mechanically, by laser energy, or chemically, by acid solution methods (22). Following introduction of the best technique to be laser AH, studies started to investigate the partial or total zona hatching on the ART outcome (23)(24)(25)(26). Additional studies on the frozen-thawed embryo cycles revealed variable results (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…For all participants with the first cycle without known poor prognosis, a gonadotropin-releasing hormone antagonist protocol was used for in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) (23). On the second day of the menstrual cycle, 150-300 IU of recombinant follicle-stimulating hormone (r-FSH) (Gonal-F™, Merck-Serono, Geneva, Switzerland) were administered, and mean follicular growth was monitored via two-dimensional trans-vaginal sonography (TVS).…”
Section: Ovarian Stimulation Protocolsmentioning
confidence: 99%
“…More recently GnRH antagonists were introduced for the same purpose, and the efficient dose is reported to be 0.25 mg, administered daily (2,18). Initially, GnRH antagonists were related to lower PRs and implantation rates (19)(20)(21)(22), but recent studies did not confirm this finding (23)(24)(25)(26), especially when care was taken to avoid prolongation of the follicular phase and initiation of ovarian stimulation with high P levels (27,28).…”
Section: Discussionmentioning
confidence: 99%